Exploring Students Perspectives On Hybrid Learning Implementation In Higher Education - Andy Endra Krisna (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
Hybrid learning, an educational approach that amalgamates traditional face-to-face instruction with technological tools, has emerged as a pivotal strategy in higher education. Contemporary pedagogical theories such as constructivism, active learning, and humanistic approaches play integral roles in shaping hybrid learning frameworks. The integration of technology within educational settings fosters a comprehensive and student-centric learning environment. Proficiency in learning design principles, motivation theories, and online learning paradigms is imperative for comprehending the intricacies of hybrid learning methodologies. This study adopts a qualitative descriptive methodology to explore students' comprehension of hybrid learning within higher education contexts. The participants of this study are first-semester English students enrolled at Widya Karya Catholic University. The research aims to offer valuable insights into pedagogical discourse and the implementation of hybrid learning strategies within higher education institutions. By shedding light on students' perspectives and experiences, this research endeavors to contribute significantly to the advancement of pedagogical practices and the refinement of hybrid learning methodologies in higher education settings.